Igor Volk: “Where aviation is, the country rises” - Nataliia Bem; Oksana Ilkova (Cхід)
At the very beginning of cosmonautics, Ukraine distinguished itself as a space state. In the field of space conquest, we had significant achievements: the Ukrainian was in outer space, the Ukrainians participated in international programs, produced space transport. Among the astronauts of the USSR, many who were born in Ukraine and made a significant contribution to the development of the world astronautics. Such personalities include the 58th cosmonaut of the USSR, the 143rd cosmonaut of the world, the Hero of the Soviet Union, test pilot Igor Petrovich Volk. The article provides some historiographical information and notes the small number of such studies on the personality of the astronaut. It is stated that materials of a journalistic and popular science character prevail among scientific achievements. In the article, the authors detail the life path of a prominent astronaut. I. Volk studied flight business in Ukraine - graduated from Kirovograd military aviation school of aviation pilots. His activity began in 1965, and from May 1965 to 2001 he worked at the MM Gromov Flight Research Institute. Igor Volk has devoted many years of his life to trial work in the sky. He had the knowledge and experience to test the corkscrew of almost all types of aircraft that were in the USSR at the time. The authors emphasized that it was he who, during the execution of the "corkscrew program" on the Su-27 aircraft, first performed the so-called dynamic braking - "put the aircraft on its tail." This aerobatic maneuver is now known as the Pugachov Cobra. Igor Volk tested in the atmosphere a prototype of the Soviet multiple spacecraft fighter. This project was defeated, but later another project was developed - Buran, the commander of which was appointed Igor Volk. As part of the development of this project from July 17th to 29th, 1984, Igor Volk made a space flight as a cosmonaut-researcher for the Soyuz T-12. Immediately after returning from flight to Earth, an experiment was conducted to control the Tu-154LL and MiG-25LL aircraft, which were approximated by the aerodynamic parameters to the "Buran". It was noted that he was at the helm of the aircraft immediately after the flight - none of the astronauts in the world did a similar task. This experiment was strictly classified. The world knew about the successful experiment only in 1988 during the press conference of the head of Glavcosm O. Dunayev. Igor Volk had a special, detailed approach to the test flights: he prepared in advance, thought over every detail, listened to the opinions of colleagues, and used their experience. He never catapulted. Well-known flight experts consider him the key figure in the development of techniques for landing aircraft under the conditions of engine failure.